The Influence of Timeliness and Volume on Online Hotel Booking Intention in Batam City - Selina; Afrina Sihombing, Dame (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
This study aims to determine the influence of the role of timeliness and volume on online hotel booking intention in Batam City. This study uses a descriptive quantitative approach. The population and sample of the research is people who live or reside in Batam City with a total of 415 respondents based on the Slovin Formula calculation. Data collection technique used involved distributing questionnaires via Google Form. Sampling was carried out by applying random sampling techniques. Data analysis used in this research uses multiple regression analysis methods using SPSS software. The research results show that timeliness and volume have a significantly influence on online booking intention. The timeliness and volume of information, comments and opinions left in large numbers as well as updating useful information can be taken into consideration by consumers in determining their intention to book hotels online. Consumers may consider the timeliness and total volume of information, messages and interactive comments from other consumers that can be found in a product or service review. Individuals looking for information will exhibit greater interest, potentially resulting in a perception of decreased risk among consumers, particularly in the case of tourism products, which are frequently intangible and distinctive.